Mnemonic strategy training of the elderly at risk for dementia enhances integration of information processing via cross‐frequency coupling. Issue 4 (15th September 2016) - Dimitriadis, Stavros I.; Tarnanas, Ioannis; Wiederhold, Mark; Wiederhold, Brenda; Tsolaki, Magda; Fleisch, Elgar
Abstract: Introduction: We sought to identify whether intensive 10‐week mobile health mnemonic strategy training (MST) could shift the resting‐state brain network more toward cortical‐level integration, which has recently been proven to reflect the reorganization of the brain networks compensating the cognitive decline. Methods: One hundred fifty‐eight patients with mild cognitive impairment (MCI) were selected and participated in 10‐week training lasting 90 min/d of memory training. They benefited from an initial and a follow‐up neuropsychological evaluation and resting‐state electroencephalography (EEG). Results: At follow‐up, MST revealed an extensive significant training effect that changed the network with an increase of synchronization between parietotemporal and frontal areas; frontal θ ‐parietal α2 causal strengthening as part of top‐down inhibitory control; enhancement of sensorimotor connections in β band; and a general increase of cortical‐level integration. More precisely, MST induced gain as an increase of the global cost efficiency (GCE) of the whole cortical network and a neuropsychological performance improvement, which was correlated with it (r = 0.32, P = .0001). The present study unfolded intervention changes based on EEG source activity via novel neuroinformatic tools for revealing intrinsic coupling modes in both amplitude‐phase representations and in the mixed spectrospatiotemporal domain. Discussion: Further work should identify whether the GCE enhancement of the functional cortical brain networks is a compensation mechanism to the brain network dysfunction or a more permanent neuroplasticity effect.